UDL-Based Infographic Instruction for Perceptual and Academic Skills in Primary-Aged Children with ASD - Shalalli, Ahmed Fadlallh; Elsayed, Mahmoud Ali; Arandas, Noha Mahmoud (Journal of Educational Science and Technology (EST), 2025)
Abstract. This study investigated the efficacy of a training program based on Universal Design for Learning (UDL) principles, employing educational infographics to address perceptual deficits and improve basic academic skills in primary-grade children with Autism Spectrum Disorder (ASD). Utilizing a quasi-experimental intensive one-group pretest–posttest–follow-up design, the research focused on a purposive sample of six children (four males, two females) aged 6–8 years. Data were collected through standardized perceptual scales and a researcher-developed assessment of literacy and numeracy. Statistical analysis revealed significant improvements in visual perception (Z = -2.201, p < .05, r_{prb} = 0.89$) and basic academic performance (Z = -2.201, p < .05, r_{prb} = 1.00). Follow-up assessments indicated that gains were maintained one month post-intervention. The findings suggest that UDL-aligned infographics facilitated perceptual integration and enhanced instructional accessibility for participants. While the limited sample size restricts broader generalizability, these results provide preliminary evidence supporting visual mediation as a strategy to bridge the perceptual-academic gap in neurodiverse learners.